Contribution of parental support and learning discipline to science learning outcomes of grade V elementary students - Fajar Ashwary; Sintha Sih Dewanti; Amanda Listiani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study analyses the contribution of learning discipline and parental support to the learning outcomes of Natural Sciences (IPA) of grade V elementary students. The study used a quantitative approach with an associative correlational design involving 60 grade V students of SDN 1 Banda Sakti in Lhokseumawe. Data were collected through questionnaires and analysed using multiple linear regression with the help of SPSS. The results revealed that learning discipline and parental support had a significant effect on science learning outcomes, both simultaneously (F = 42.668; p < 0.05) and partially. An R² value of 0.600 indicates that the two variables together explain 60% of the variation in students' science learning outcomes. Regression coefficient analysis also revealed that learning discipline had a more dominant influence (β = 0.576; t = 6.836; p < 0.05) compared to parental support (β = 0.465; t = 5.516; p < 0.05). These findings confirm that strengthening learning discipline needs to be the main focus of educational interventions, in addition to increasing school-family collaboration in creating a learning environment that supports students' academic success.